2014
DOI: 10.3109/14767058.2014.929659
|View full text |Cite
|
Sign up to set email alerts
|

Systematic use of the RAM nasal cannula in the Yale–New Haven Children’s Hospital Neonatal Intensive Care Unit: a quality improvement project

Abstract: RAM NC use with NIV was well tolerated in the neonatal population with the use of our guidelines. We speculate that use of our guidelines will lead to a more systematic use of the RAM NC in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 9 publications
1
33
1
Order By: Relevance
“…There usually was no need to provide pressure relief with the RAM system, however, we used it for extended periods of time in our extremely low birthweight population, which explains the occurrence of any lesion with this interface. When contrasting our results with the Nzegwu et al 16 study, which found no new lesions with the use of the RAM system for Ͻ 10 d in low birthweight (1.29 Ϯ 0.8 g) infants, our subjects on the RAM system were treated for an average of 37.9 Ϯ 12 d, and weighed less (884 [range 497-1365] g).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There usually was no need to provide pressure relief with the RAM system, however, we used it for extended periods of time in our extremely low birthweight population, which explains the occurrence of any lesion with this interface. When contrasting our results with the Nzegwu et al 16 study, which found no new lesions with the use of the RAM system for Ͻ 10 d in low birthweight (1.29 Ϯ 0.8 g) infants, our subjects on the RAM system were treated for an average of 37.9 Ϯ 12 d, and weighed less (884 [range 497-1365] g).…”
Section: Discussioncontrasting
confidence: 99%
“…[13][14][15] Clinically, only one observational study was found that reviewed a single center's experience when substituting the RAM for a conventional noninvasive respiratory support interface using 2 ventilators with different flow-generation characteristics. 16 The investigators used the RAM to reduce the impact of tissue breakdown and agitation that resulted from conventional noninvasive respiratory support interfaces and found that most infants were successfully weaned by using the RAM cannula with NIV or CPAP. 16 However, this study did not report outcomes with the RAM compared with other interfaces or between ventilators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 There is also a move toward the use of modified RAM to deliver NCPAP and NIPPV. 27,28 However, to date, there is little clinical evidence of its physiological and clinical impact when delivering NIPPV. Further research is needed to understand the mechanics as well as clinical impact of such interfaces before their routine use for NIPPV can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A next-generation nasal cannula (RAM cannula, Neotech, Valencia, California) has recently been used as an interface to provide noninvasive ventilatory support, such as nasal intermittent positive-pressure ventilation, CPAP, and noninvasive neurally adjusted ventilatory assist. 10 The impact of the Neotech RAM cannula on the delivery of pressure and V T needs to be studied to allow clinicians and therapists to use the cannula effectively.…”
Section: Introductionmentioning
confidence: 99%